Fiber-reinforced concrete for the flat bottom of silos - Rodrigo A. Constantino; José P. Lopes Neto; Marcilene V. da Nóbrega; José W. B. do Nascimento; Jefferson H. G. da Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The use of synthetic fibers as reinforcement for concrete replacing the steel reinforcement has been diffused worldwide in several applications, gaining prominence in the application for industrial floors, tunnel linings, road pavements, etc., i.e., continuous structures in contact with soil that require performance in the elastic medium. The present study investigated the applicability of concrete reinforced with synthetic fibers in the bottom slab of silos supported directly on the ground, being composed of an experimental study and a case study. The experimental study consisted of the analysis of the mechanical behavior of this concrete by testing three concentrations of synthetic fibers (3.0, 4.5 and 6.0 kg m-3) in a conventional simple concrete matrix. The case study consisted of the design of this part in conventional reinforced concrete and concrete reinforced with synthetic fibers with the objective of performing an economic comparison between the two projects. The experimental results showed that the fiber concentration that contributed to a better mechanical performance of the concrete matrix was 3.0 kg m-3. The case study showed that the most economical design was the one made with fiber-reinforced concrete.